Nutritional Status in Childhood Thalassaemia at the-Department of Child Health University of North Sumatera Dr. Pirngadi Hospital Medan - Ismet Fadil Loebis; Sugiani Sinulingga; Adi Sutjipto (Paediatrica Indonesiana, 1991)
A-10 year (June 1979 to May 1989) study on the nutritional status of children with thalassaemia was done. The number of patients was 131; 75 (57.25%) were males and 56 (42. 75%) females. A study on nutritional status by the age group was performed in 123 cases at the first diagnosis. The incidence of malnourished children over 1 year of age was significantly higher than in below 1 year of age cases (p < 0.05).